The Altruism in action on Deadpool 2 movie script - Wa Sari Sari (ELITE: Journal of English Language and Literature, 2016)
This research aimed to how altruism in action is done by Wade’s main character through Deadpool 2 movie script by Batson theory (1995). Data from altruism in action is grouped by a chart. The researcher thereafter analyzes aspects of altruism based on aspects of liabilities, motive, and benefit. The researcher uses this aspect of liabilities, motive and benefit in the Deadpool 2 movie script analysis becausethe speech about the three aspects falls into the main character. It can be seen as Wade saved Russell from the fire that the Cable did save him from that act, spared aven the death that he looked upon back then, he was willingto sacrifice himself for the safety of others, taking responsibility for what he was responsible. So he had to be done, and that can benefit others. Data analysis shows the main character in the Deadpool 2 movie script.